The Dynamics of Consumer Spending in the COVID-19 Pandemic - Musbatiq Srivani; Ranny Fitriana Faisal (Qubahan Academic Journal)
This cross-sectional research was conducted with the goal of assessing the Marginal Propensity to Consume (MPC) among individuals residing at regional level, both prior to and in the midst of the COVID-19 pandemic. The study aimed to gain an understanding of the significance of the MPC values. These MPC values serve as a reflection of the spending tendencies of the West Sumatra population, providing valuable insights into consumer behavior during distinct time periods. For this study, data was gathered using online surveys that were distributed to chosen samples across different regions and urban areas in West Sumatra. The analysis relied on the Ordinary Least Squares Method. The findings of the research highlight a significant contrast in MPC values prior to and amid the COVID-19 pandemic. To be precise, the MPC value was higher before the pandemic compared to what was observed during the pandemic. This difference can be attributed to increased economic uncertainty during the pandemic, which led to a reduction in autonomous consumption. Additionally, this research goes beyond exploring spending habits by investigating the portion of income dedicated to consumption prior to and amidst the COVID-19 pandemic. The results reveal that the percentage of income directed towards consumption during the pandemic is less than what was observed before the pandemic. These outcomes are in harmony with economic theories and underscore the influence of uncertain circumstances on how consumers allocate their funds.